Time-frequency analysis of power signal : application to substation monitoring and management system - Ismail, Kamarul Afizam; Salleh, Sh-Hussain; Mokji, M. M.; Saeli, Ronisham; Ghani, A.; Yusof, M. (IEEE, 2005)
This paper presents a power disturbance detection and classification method based on Time-Frequency analysis. We will discuss how the choice the kernels affect the characteristic of the distribution function. Here we consider a non-stationary testing harmonic composed of a fundamental frequency of 50Hz and its second and third harmonic frequency components. The 50Hz signal is on for the entire record extending from 0 to 1second, while the 100Hz signal is from 100ms to 350 ms and 200Hz signal is from 200ms to 550ms. As for comparison, we will use the same testing signal for different type of kernels. This technique has been applied in a substation monitoring and management system which monitors the power quality at the substation as well as the street lighting panel.